Kinetic Catalytic Method for the Estimation of Mn(II) - Fadnis, G.; Tenson, P.A. (Asian Journal of Chemistry, 2010)
Mn(II) has been estimated in simulated samples by kinetic catalytic method using D-glucose-Ce(IV) redox indicator reaction in sulphuric acid medium. The estimation have been made from the calibration plots obtained by using pseudo first order rate constant data of the indicator reaction and also by fixed time and fixed concentration procedures at different ppm concentration of Mn(II). The results of this study indicate that the estimated values of the simulated samples are consistent and responsible.